Physical match demands across different playing positions during transitional play and high-pressure activities in elite soccer - Bortnik, Lukasz; Bruce-Low, Stewart; Burger, Joost; Alexander, Jill; Harper, Damian; Morgans, Ryland; Carling, Christopher; McDaid, Kevin; Rhodes, David (Biology of Sport, 2024)
This study explored physical match demands across different playing positions during transitional play, to inform the need for position-specific training interventions. Data was collected using 10 Hz GPS units from 10 competitive matches including 23 elite soccer players of the 1 st Polish Division (Ekstraklasa) in season 2020–21. A total of 4249 positional observations were made; center backs ( n = 884), full backs ( n = 972), central defensive midfielders ( n = 236), central attacking midfielders ( n = 270), central midfielders ( n = 578), wingers ( n = 778), and attackers ( n = 531). Match data reflected distances covered per minute (m·min−1): total distance (TD), high-speed running distance (HSRD, > 19.8 km·h −1 ), sprint distance (SD, > 25.2 km·h −1 ), and the frequency of high-intensity accelerations and decelerations (A+D, > 3 m·s −2 ; n·min −1 ). Total absolute sprint distance (SD, > 25.2 km·h −1 ) and total relative sprint distance (Rel B5) were also quantified. A univariate analysis of variance revealed position-specific differences. Significant effects of position were found for all analysed metrics during transitional play (large ESs; p < .001). Central attacking midfielders displayed higher TD (m·min −1 ), fullbacks covered highest SD (m·min −1 ) and wingers achieved the highest A+D (n ·min −1 ) ( p ≤ 0.05). Centre backs displayed the lowest physical outputs when compared to all other positions, except in A+D (n ·min −1 ) during defensive transitions ( p ≤ 0.05). Attackers displayed the highest physical metrics during high pressure activities ( p ≤ 0.05). Coaches should carefully consider positional transitional demands to better inform training design. With specific attention paid to drills that replicate game play.